2013
DOI: 10.5812/traumamon.10541
|View full text |Cite
|
Sign up to set email alerts
|

Fine Needle Aspiration: An Atraumatic Method to Diagnose Head and Neck Masses

Abstract: BackgroundPatients presenting with a mass require tissue biopsy for histological diagnosis and treatment. Fine needle aspiration (FNA) is offered as an atraumatic, well tolerated, and inexpensive method for obtaining a biopsy from these lesions.ObjectivesIn this study we evaluated the accuracy of FNA as an atraumatic method among patients with nonthyroidal masses for diagnosis of neoplastic masses compared to open surgery.Patients and MethodsIn a cross-sectional study, 65 patients with a head and neck masses (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
3
10
0
Order By: Relevance
“…In regard to the diagnostic accuracy of fine-needle aspiration cytology in differentiating malignant and benign lesions, we found a Se of 78.1% and a Sp of 76.5%. Similar studies reported Se between 82.14% and 95%, and a Sp of 62.7% to 100%; [ 3 , 6 , 8 , 17 , 21 , 22 , 32 34 ] thus our results are in line with those found in the literature.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In regard to the diagnostic accuracy of fine-needle aspiration cytology in differentiating malignant and benign lesions, we found a Se of 78.1% and a Sp of 76.5%. Similar studies reported Se between 82.14% and 95%, and a Sp of 62.7% to 100%; [ 3 , 6 , 8 , 17 , 21 , 22 , 32 34 ] thus our results are in line with those found in the literature.…”
Section: Discussionsupporting
confidence: 93%
“…We found a female:male ratio of 1:1.4 for patients with lateral cervical masses, similar to the results reported by Manjula et al [ 17 ] and Akhavan-Moghadam et al [ 6 ] in their series of 386 and 65 patients, respectively. Still, many clinical studies reported uneven data regarding gender distribution of lateral cervical masses; in their extensive study of 850 cases, Modi et al [ 18 ] found a female:male ratio of 1.06:1, whereas Soni et al [ 3 ] described the involvement of 66.15% female patients and 33.89% males in their study of 59 cases.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations